ANALISIS KEMAMPUAN MAHASISWA DALAM MENERAPKAN KETERAMPILAN PROSES IPA DALAM PEMBELAJARAN PADA MATA KULIAH METODOLOGI IPA MI - Muhamad Afandi (JIP Jurnal Ilmiah PGMI, 2018)
This research aims to describe: the application, ability, and problems experienced by PGMI students in applying the science process skills approach to learning practices in the MI science learning methodology courses. This research method uses a qualitative approach with the type of descriptive research or also called qualitative descriptive research. Data collection techniques use observation, interviews, and documentation. Checking the validity of the data uses persistence of observation, triangulation, and referential adequacy. Data analysis uses percentages then processed through data reduction, data presentation, drawing conclusions and verification. The results of this research include: (1) The application of the skills approach to the IPA process is carried out through the following steps: dividing students into several groups, determine and develop MI science learning material, prepare learning media or teaching aids for MI science, make plans for MI science learning, develop instruments for evaluating the results of MI science learning, and apply the science process skills approach (observe, predict, classify, measure, conclude, and communicate) with the peer teaching method; (2) The ability of PGMI students to apply the science process skills approach to learning in MI science methodology courses is good; (3) Problems experienced by PGMI students in applying the science process skills approach include: less optimal learning planning, students still have difficulty in designing learning, lack of media or teaching aids, and mastery of material that is less than optimal.